2019
DOI: 10.1371/journal.pbio.3000256
|View full text |Cite
|
Sign up to set email alerts
|

Feminizer and doublesex knock-outs cause honey bees to switch sexes

Abstract: Honey bees are experts at refuting societal norms. Their matriarchal hives are headed by queens, backed by an all-female workforce, and males die soon after copulation. But the biochemical basis of how these distinct castes and sexes (queens, workers, and drones) arise is poorly understood, partly due to a lack of efficient tools for genetic manipulation. Now, Roth and colleagues have used clustered regularly interspaced short palindromic repeats (CRISPR) to knock out two key genes ( feminizer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…For example, CRISPR has recently been used to knockout two sex‐determining genes in A. mellifera causing individuals to change gender (Mcafee et al. ). This technology has also been adapted to be able to change the methylation state of a given loci (Vojta et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CRISPR has recently been used to knockout two sex‐determining genes in A. mellifera causing individuals to change gender (Mcafee et al. ). This technology has also been adapted to be able to change the methylation state of a given loci (Vojta et al.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should focus on the consequences of experimental methylation removal or addition (Pegoraro et al 2017), as well as exploring additional epigenetic mechanisms to attempt to identify a full pathway leading to reproductive caste differences. For example, CRISPR has recently been used to knockout two sex-determining genes in A. mellifera causing individuals to change gender (Mcafee et al 2019). This technology has also been adapted to be able to change the methylation state of a given loci (Vojta et al 2016), allowing the possibility of exploring the function of methylation in specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…The accession for HSP70 is NP_001153536.1. Bee silhouettes are adapted from McAfee et al (2019) 84 (CC-BY 4.0).…”
Section: Resultsmentioning
confidence: 99%
“…These proteins determine male and female development, respectively. The function of dsx has been explored in several insects, including Drosophila (Shirangi et al, 2016), beetles (Ledón-Rettig et al, 2017), Bombyx mori (Xu et al, 2017), A. gambiae (Kyrou et al, 2018), and honey bees (McAfee et al, 2019). Previous studies have suggested that lncRNAs can regulate neighboring coding genes (Villegas and Zaphiropoulos, 2015).…”
Section: Discussionmentioning
confidence: 99%